Evaluation of Cephalometric Downs Analysis on Cephalograms at RSGM YARSI, Jakarta - Puspitasari, Ayu Laksmi; Siregar, Fazwishni (YARSI Dental Journal, 2024)
Introduction: Cephalometric analysis is used to help establish diagnosis and treatment plan in orthodontics. One of the cephalometric analysis is the Downs analysis which its standard values were measured in Caucasians. However, these values cannot be applied to other races and ethnicities because there are racial and ethnic variations. Hence, it is necessary to know the average value for Indonesians. Objective: This study aimed to evaluate Downs analysis on cephalograms at RSGM YARSI Jakarta, compare it with Downs’ norms and other ethnicities, and determine differences between gender. Materials and Methods: Measurements of 10 parameters of Downs analysis were carried out on 29 cephalograms. Data were tested statistically. Results: The mean of the facial angle are 85.17°±3.07; angle of convexity 3.62°±2.79; AB plane angle AB -2.65°±2.55; mandibular plane angle 29.82°±3,37; Y-axis 64.15°±3.34, occlusal plane angle 11°±2.86; interincisal angle 113.06°±7.64; LI-occlusal angle 28.41°±5.24; IMPA angle 10.24°±5.76; distance of UI-APog 8.05 mm±1.85. Discussion: The RSGM YARSI cephalometric value compared to the Downs’ norms shows that the chin towards the FHP is more retroposition, the face is more convex, the relationship of the lower and upper jaw to the NPog is more protrusive, the direction mandibular growth towards the FHP is more vertical, the direction of facial growth is more downward, occlusal growth towards the FHP is steeper, and the incisors are more protruded. The direction of growth in male is more vertical than in female, and there are differences in cephalometric values with other races. Conclusion: There is a significant difference between the Downs cephalometric values of RSGM YARSI and the Downs’ norms in all measurements. Between men and women at RSGM YARSI there are gender differences in the direction of growth. There are differences in measurement values with other races.